Push-over analysis of concrete gravity dams due to flood inflow - Mohammad Reza Gavzan Daroonkola; Mohammad Taghi Ahmadi (Numerical Methods in Civil Engineering)
This study numerically predicts the failure scenario of a cracked concrete gravity dam through a push-over nonlinear analysis. The mixed-mode Linear Elastic Fracture Mechanics (LEFM) was employed using the extended finite element method (XFEM). The dam base was considered to be fully fixed without any foundation effects. The hydrostatic pressure on the dam's upstream face was increased incrementally. The failure scenario type of the concrete gravity dams with an initial crack at an arbitrary level exhibited a ductile manner. A mixed-mode crack path with a positive mode II was observed in all initial crack levels. Based on the results, it can be claimed that provided water intrusion prevented, "cracked" concrete gravity dams may not be at noticeable risk of failure due to flood inflow.